The effect of using virtual simulation programs across the flipped classroom on developing genetic problem-solving skills and future thinking among secondary school students Bisha Governorate - Elazzab, Eman Saber Abdelkader (Journal of Curriculum and Teaching Methodology, 2022)
The aim of the research is to investigate the effect of using virtual simulation programs across flipped classrooms in the biology course (3) in developing genetic problem-solving skills and future thinking among a sample of (43) female students of the third year of secondary school specializing in scientific courses, which represents the experimental group, and (42) students with the same The class taught in the usual way represents the control group, and the genetic problem solving skills test and future thinking skills test were applied to the two groups, before and after, and the results showed the effectiveness of using virtual simulation programs across flipped classes in developing genetic problem solving skills and future thinking, and the research recommended the need to train teachers on Develop these skills among learners.